Flora of Bahia – Caryophyllaceae - Carneiro, Cláudia Elena; Furlan, Antonio (SITIENTIBUS série Ciências Biológicas, 2006)
This paper presents a survey of the species of Caryophyllaceae in Bahia State, Brazil. Four species are listed: Drymaria cordata (L.) Willd. ex Roem. & Schult., Paronychia camphorosmoides Cambess., Polycarpaea corymbosa (L.) Lam., and Stellaria media (L.) Vill. Descriptions, illustrations, comments, and key for taxa are presented.